Evaluation of alfalfa (Medicago sativa L.) populations’ response to salinity stress - Cornacchione, Monica; Suarez, Donald L. (2018)
Alfalfa (Medicago sativa L.) is a moderately salt-tolerant crop with high economic return and is therefore more suitable for production with lower quality water than most high-value crops. This study was conducted to examine the effect of water composition types (Cl− or SO42−) of irrigation water and five salinity levels (electrical conductivity of irrigation water [ECiw] = 0.85, 8, 13, 18.3, and 24.5 dS m−1) on biomass production, salt tolerance, and ion concentration of 15 alfalfa populations. The plants were grown in a greenhouse in 60 sand tanks for 347 d under salt treatment. There was no significant effect of water composition type on shoot and root biomass production. Water composition type × EC and water composition type x population interactions were also not significant. Salinity impact was population dependent (EC × population: P < 0.05), except at ECiw 18.3 dS m−1. Across all populations, shoot biomass was significantly reduced with increasing salinity to 77, 50, and 27% of the control at 13, 18.3, and 24.5 dS m−1, respectively. The ‘SISA14’ and ‘SW 8421S’ populations were the most productive under saline conditions with the highest degree of salt tolerance. The results showed that alfalfa biomass response to salinity did not depend on the type of salts (Cl− or SO42−). Shoot Cl− also did not correlate with relative biomass response. Thus, Cl− ion toxicity does not appear to be a factor in alfalfa salt tolerance for these populations. Although there was a correlation between salt tolerance and shoot Na+, the shoot ion concentration provides only a partial explanation of the relative salt tolerance of the alfalfa populations.